The Glutathione/Metallothionein System Challenges the Design of Efficient O2‐Activating Copper Complexes. (18th March 2020) - Santoro, Alice; Calvo, Jenifer S.; Peris‐Díaz, Manuel David; Krężel, Artur; Meloni, Gabriele; Faller, Peter
Abstract: Copper complexes are of medicinal and biological interest, including as anticancer drugs designed to cleave intracellular biomolecules by O2 activation. To exhibit such activity, the copper complex must be redox active and resistant to dissociation. Metallothioneins (MTs) and glutathione (GSH) are abundant in the cytosol and nucleus. Because they are thiol‐rich reducing molecules with high Cu I affinity, they are potential competitors for a copper ion bound in a copper drug. Herein, we report the investigation of a panel of Cu I /Cu II complexes often used as drugs, with diverse coordination chemistries and redox potentials. We evaluated their catalytic activity in ascorbate oxidation based on redox cycling between Cu I and Cu II, as well as their resistance to dissociation or inactivation under cytosolically relevant concentrations of GSH and MT. O2 ‐activating Cu I /Cu II complexes for cytosolic/nuclear targets are generally not stable against the GSH/MT system, which creates a challenge for their future design. Abstract : Designstudie : Kupferkomplexe sind von medizinischem und biologischem Interesse, z. B. als Tumortherapeutika. O2 ‐aktivierende Cu I /Cu II ‐Komplexe für Zielstrukturen im Zytosol oder Zellkern sind generell nicht stabil gegen Glutathion und Metallothioneine, die dort häufig vorkommen. Dies ist beim Design von Cu I /Cu II ‐Komplexen für biologische und medizinische Anwendungen zu bedenken.